2017
DOI: 10.1186/s13256-017-1456-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of high doses of vasopressin and corticosteroids in a patient with Crohn’s disease with refractory septic shock after intestinal perforation: a case report

Abstract: BackgroundIn this article, we present a clinical case of refractory septic shock resulting from intestinal perforation treated with high doses of vasopressin and hydrocortisone during emergency surgery.The use of such high doses of vasopressin for this type of shock is not described in the literature.Case presentationA 49-year-old white woman with grade III obesity, Crohn’s disease, and an intestinal perforation presented with refractory septic shock. Initially, a low dose of vasopressin was used. Then, the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Corticosteroids are drugs with multiple adverse effects, such as bacterial super-infection, cardiovascular complications, and hyperglycemia risk, and should be used cautiously in severe patients, hypoxic patients, and patients with a history of glucocorticoids use (260) . In the term of methylprednisolone, it has been shown that it should be used in a dosage less than 1 mg/kg/day and not be used for more than one week (181) and IV dexamethasone must be used with a dosage of 6mg/day in COVID-19 patients (261) . Another severe complication of corticosteroid use is intestinal perforation which is related to the high dose of corticosteroids.…”
Section: Clinical Considerations and Future Prospectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids are drugs with multiple adverse effects, such as bacterial super-infection, cardiovascular complications, and hyperglycemia risk, and should be used cautiously in severe patients, hypoxic patients, and patients with a history of glucocorticoids use (260) . In the term of methylprednisolone, it has been shown that it should be used in a dosage less than 1 mg/kg/day and not be used for more than one week (181) and IV dexamethasone must be used with a dosage of 6mg/day in COVID-19 patients (261) . Another severe complication of corticosteroid use is intestinal perforation which is related to the high dose of corticosteroids.…”
Section: Clinical Considerations and Future Prospectivesmentioning
confidence: 99%
“…Another severe complication of corticosteroid use is intestinal perforation which is related to the high dose of corticosteroids. A study reported a 66-year old man with metabolic syndrome and COVID-19-associated acute respiratory failure under treatment with high dose methylprednisolone and TCZ to be diagnosed with acute intestinal perforation (261) . Since other studies had previously reported the same complication in RA patients treated with TCZ/corticosteroids [262] , [263] , intestinal perforation must be considered as a lethal complication of treatment with corticosteroids and TCZ in COVID-19 patients.…”
Section: Clinical Considerations and Future Prospectivesmentioning
confidence: 99%
“…MCPP,2,4–Dなどのフェノキシ酸系除草剤は薬物動態が似ているため,種類によらず,フェノキシ酸系除草剤として中毒機序や治療法が報告されている 9), 10)。フェノキシ酸系除草剤の中毒機序は,大きく3つある。第1は,容量依存性に細胞膜障害を引き起こすことであり,2,4–Dと2,4,5–trichlorophenoxyacetic acid(2,4,5–T)により障害されやすいとされている 10)。第2は,アセチルCo–A類似化合物として作用することである 10)。アセチルコリン合成経路に取り込まれ,コリン作動性物質として,ムスカリン作用とニコチン作用を起こす 10)。本症例では縮瞳を認めており,中毒物質によるムスカリン症状と考えられたが,フェニトロチオンも服毒していたため,MCPPによる縮瞳とは結論づけられなかった。第3に,酸化的リン酸化反応の脱共役剤として作用し,アデノシン三リン酸(adenosine triphosphate: ATP)合成を阻害することである 10)。ATP合成が阻害されると,ATP依存性Kチャネルの活性化を引き起こす。これは,敗血症性ショックのときに血管収縮薬抵抗性の血管拡張を生じる要因の1つと同様の機序である 11)。本症例の循環不全も血管分布異常性ショックによる循環不全であり,フェノキシ酸系除草剤中毒の機序と矛盾しない。DOBとNAが奏功せずVPを加えて循環は安定したが,これはVP単独の効果というより,DOB,NAとの相乗作用と考えられた 12)。VPに関しては,敗血症性ショック患者にNAのみで対応した群と,NAとVPで対応した群の,後者のほうで28日と90日死亡率が低下したという報告がある 13)。一方,VPを単独早期投与しても予後改善効果は明確でなかった報告もあり 14),フェノキシ酸系除草剤の循環不全には,NAを基本としていくつかの血管収縮薬を使用することが望ましいと考えられる。中村らは,2,4–D中毒で高度な循環不全を来した症例に対して,NAに加えてVPの速やかな使用が,良い転帰をもたらしたと報告している 15)。…”
Section: 考  察unclassified
“…Septic shock is the most common critical illness in intensive care unit (ICU), with long hospital stay, high cost, and high mortality ( 1 3 ). Intestinal perforation is one of the important causes of septic shock ( 4 , 5 ). Sepsis leads to complications in coagulation patients ( 6 ).…”
Section: Introductionmentioning
confidence: 99%